Agama dan Kekuasaan (Studi pada Gerakan Sosial Keagamaan Warga Al-Khairiyah Cilegon-Banten) - rafiudin rafiudin (Departement of History and Islamic Civilization, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2020)
Al-Khairiyah, which is in the form of a Community Organization (ORMAS), runs organizational programs that focus on the donation program as a superior program in helping Madrasas. This study uses a qualitative method by analyzing organizational movements ranging from social assistance towards a practical political level. The ideological movement based on religious values ​​towards the realm of power creates a problem formulation regarding the relationship between religion and power. The attachment that exists as a logical consequence is the aim of this study. The institutional peak through which the mass organization Al-Khairiyah has been dominated by its achievements is due to the ability of the general chairman, H. Ali Mujahidin in managing the organization in a relatively short period of time starting in 2016 is a typical indication of a Social Movement as a result of research